THE 1st BABY CAMP FOR BABIES WITH VISUAL IMPAIRMENT IN BANDUNG – INDONESIA (Proceedings of International Conference on Special Education, 2017)
Young children with visual impairment are spread out across different cities in Indonesia; unfortunately, there is a limited numbers of early intervention programs (EIP) to provide services to the children and their families. Parents feel isolated. Initiatives have been taken to solve this crisis. Perkins International has started to provide support for the development of an EIP, online support to parents, materials for learning and others. In partnership with local organizations, Perkins initiated a “Baby Camp” workshop for families aimed to build relationships among the families. The Baby Camp included opportunities for parents to share feelings, ideas and challenges and most importantly, ways of helping parents create their dreams for their child with disability and their family. 17 families & 5 Perkins International partners attended the 3 day Baby Camp. Various topics and activities on babies and families were covered, such as: feeding preparation, developing gross and fine motor skills, self-help and other strategies. Parents learned to make toys out of available materials; set-up different play corners and activities. Parent happiness is also our concern, as this affects their connection with their child. With this in mind, we created some fun and silly games for families to help them re-discover their joy. The impact of this event is very significant; the Indonesia parent group was established. The event resulted in parents having stronger connections to actively support each other. They gained confidence in raising their children and advocating for them. In this presentation, we also will share many beautiful pictures of the event and testimony from the families.